FRESH, PSEUDOTACHYLYTE-BEARING MANTLE PERIDOTITES FROM THE LAWSONITE ECLOGITE-FACIES SAN PETRONE UNIT, ALPINE CORSICA - Vitale Brovarone, Alberto; Piccoli, Francesca; Frasca, Gianluca; Giuntoli, Francesco (Ofioliti, 2021)
Mantle peridotites exhumed in mountain belts provide important insights on the composition and evolution of the upper mantle, and additionally inform on metamorphic, geochemical, and tectonic processes -including seismic activity- at convergent margins. In this contribution, we present field, microstructural, and mineralogical data of fresh, pseudotachylyte-bearing mantle peridotites from the lawsonite eclogite-facies San Petrone unit, Alpine Corsica, France. The present case study represents the first example of subducted fresh peridotite associated with fresh lawsonite eclogite-facies assemblages. Two bodies of fresh peridotite are embedded in fully serpentinized ultramafic rocks forming the substratum of a subducted ocean-continent transition of the Piemonte-Liguria Basin. Clinopyroxene and spinel mineral chemistry indicates that the investigated peridotite samples were part of a refertilized mantle and, therefore, the San Petrone unit likely belonged to the more distal part of the ocean-continent transition. Because small bodies of fresh peridotite embedded in fully serpentinized rocks can hardly be identified by means of geophysical investigations, this finding suggests that small, yet disseminated bodies of fresh mantle peridotite can potentially be more abundant than previously supposed at ocean-continent transition and, potentially, at mid-ocean ridges and in subduction zones. The preservation of fresh mantle peridotite bodies in subducting slabs is also discussed with respect to its potential implications on intermediate depth seismicity and geochemical cycling -including production of natural energy sources- from rifting to subduction.